Identifikasi Pengaruh Umur Simpan dan Antioksidan Terhadap Kandungan Karbohidrat dan Kadar Air Pada Mie Tapioka Basah - Juwitaningtyas, Titisari; Nurul Khairi, Amalya (Universitas Ahmad Dahlan, 2018)
Wet tapioca noodles are a typical food in one of the regions in DIY Province. Traditional processing results in a limited shelf life. Gambir (Uncaria gambir roxb) plants are popular plants to be processed into herbal medicines and nutritious plants. Based on research, gambir has the ability as an antimicrobial and natural antioxidant because of the content of catechins in it. This study aims to identify the effectiveness of using gambir extract as a natural antioxidant in wet tapioca noodle samples. The methodology in this study was carried out by mixing 7% gambir extract into 50 grams of wet tapioca noodles. The finished sample is then treated with storage for 0 days, 3 days, and 5 days. The result of the analysis are in 0 day storage, sample contains antioxidant 80,624 ic50, carbodydrate 41,048 mg, and water 58,575 %. In 3 days storage, sample contains antioxidant 91,048 ic50, carbohydrate 45,744 mg, and water 53,415 %. In 5 days storage, sample contains 94,876 ic50, carbohydrate 60,547 mg, and water 39,100 %. Based on the tests conducted, it appears that there is an increase in the number of antioxidants during the storage period. This is accompanied by increasing carbohydrate content and decreasing water content. Decreasing water content will have an impact on the stability of microbial activity so that it extends shelf life. These results provide the conclusion that gambir extract can provide a longer shelf life effect.